x/3+2-9/6+x/6-1

Simple and best practice solution for x/3+2-9/6+x/6-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x/3+2-9/6+x/6-1 equation:


x in (-oo:+oo)

x/3+x/6-(9/6)-1+2 = 0

x/3+x/6-3/2-1+2 = 0

1/2*x-1/2 = 0 // + 1/2

1/2*x = 1/2 // : 1/2

x = 1/2/1/2

x = 1

x = 1

See similar equations:

| -5f-7+3.5=26.5 | | 6/7y+1/6(y-7)=y+1/7 | | 3x-5/10=7 | | 19+5/x=6 | | X+0.2x=24 | | 2y-3= | | 2.5(x+1)=1.5x | | 15.3=(-7.5k)+55.2 | | 0.7(6x+9)=3.4-(x-3) | | W/2.5=0.7 | | 2.33x+10+5.66x-9.5=12.5 | | 4x=8x+12x-16y | | M^2*m-30=0 | | 17(t-6)+4t=7(3t+4)-9 | | 2k^2-k-36= | | a/25=25 | | -5+8+-13= | | 2-4x=50 | | 0=x^4-29x^2-252 | | 2x-8+x=21 | | 2^(1/x)=0 | | 2^(1/x) | | 2/3x-2/3-2/5x+3/5-1 | | 2/x+3=5/2x+13/4 | | 7+3t-5=7t+10-3t | | 5+8+-13= | | 1.5x=15.17 | | 180=(x+3)+(2x-61) | | x-4.72=5.28 | | 7(t-4)+8t=5(3t+3)-11 | | 27-55= | | 3n^4-33n^2+30= |

Equations solver categories